THE NUTRITIONAL STATUS OF RIVERINE CHILDREN AGED 0 TO 2 IN THE NORTH OF THE COUNTRY (Editora Impacto Científico, 2025)
The aim of this study was to describe the nutritional status of riverine children aged 0 to 2 in the northern region of Brazil in 2024, based on data provided by the Food and Nutrition Surveillance System (SISVAN). This is a descriptive-epidemiological study, with a quantitative approach, carried out using secondary data collected from the SISVAN database in June 2025. Variables such as gender, age group, weight, race/color, community and region were analyzed, with descriptive statistical treatment using BioEstat 5.3 and Microsoft Excel software. The results showed that, of the seven states in the North, only Pará and Amazonas had records of children's nutritional status. Most of the children analyzed showed adequate weight for their age, with a slight occurrence of low weight and high weight, especially in the state of Pará. The brown race was the most prevalent among the records. Despite the apparently satisfactory scenario among the available cases, the data is still scarce and does not allow generalizations to be made about the nutritional reality of riverine children in the northern region as a whole. The low coverage of SISVAN, combined with geographical, social and cultural factors, makes it difficult to monitor and formulate more effective public policies. The study highlights the need to broaden the scope of nutritional surveillance and strengthen health actions aimed at vulnerable populations.